2018
DOI: 10.1186/s12931-018-0920-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of lung function with cardiovascular risk: a cohort study

Abstract: BackgroundThe potential effects of pulmonary dysfunction on cardiovascular diseases (CVD) are receiving attention. We aimed to investigate and quantify the cross-sectional and longitudinal associations between lung function and overall cardiovascular risk among Chinese general population.MethodsWe studied 4019 participants from the Wuhan-Zhuhai cohort, with a follow-up of 3 years. A multivariable risk algorithm generated from the Framingham study was used to calculate individuals’ overall cardiovascular risk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…It is not fully understood how COPD and CVD are linked beyond their shared risk factors but researchers have identified a number of possible mechanisms such as hypoxia and oxidative stress that might be involved [9,10]. Furthermore, numerous studies have reported the existence of associations between various measures of impaired lung function, including low FEV 1 , FVC and FEV 1 /FVC, and an increased likelihood of developing CVD, as well as an increased risk of hospitalisation and death secondary to CVD [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is not fully understood how COPD and CVD are linked beyond their shared risk factors but researchers have identified a number of possible mechanisms such as hypoxia and oxidative stress that might be involved [9,10]. Furthermore, numerous studies have reported the existence of associations between various measures of impaired lung function, including low FEV 1 , FVC and FEV 1 /FVC, and an increased likelihood of developing CVD, as well as an increased risk of hospitalisation and death secondary to CVD [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization reported that more than 80% of adolescents and 25% of adults are insufficiently physically active (PA) [1]. Lung function such as forced expiratory volume in 1 s (FEV1) or forced vital capacity (FVC) is an important predictor of morbidity of cardiovascular diseases (CVD), type 2 diabetes, cognitive disorders, disability, as well as all-cause mortality [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, lung function impairment also played an important role in the association of asthma with CVD risk 27 , 28 . Long-term airway remodeling in those with asthma, could induce irreversible airway obstruction and lead to lung function impairment.…”
Section: Discussionmentioning
confidence: 99%